The Effect of Recruitment and Selection on The Performance of Technician Employees - Pancasasti, Ranthy (Management Science Research Journal, 2023)
Background: In an organization or company to determine the position of the right person in filling a position, if the position is not made within a clear boundary and involves the scope of the position and the specifications of the holder of the position. Which can be used as the basis for recruitment and selection. With the recruitment and selection, the prospective employees who are accepted are in accordance with the criteria needed in an organization. Purpose: The purpose of this study is (1) to determine the effect of recruitment on employee performance partially, (2) to determine the effect of selection on employee performance partially and (3) to determine the effect of recruitment and selection on employee performance simultaneously. Design/methodology/approach: The method that has been used in this research is quantitative associative method and the primary data source is using the type of questionnaire instrument. The population in this study were employees technision of PT. XYZ as many as 56 respondents. The sampling technique used is a saturated sample or often referred to as a total sample. The analytical technique used in this research is Partial Least Square (PLS) which includes convergent validity, discriminantt validity, composite reliability, cronbach alpha, R-square, simulant test (F test), and partial test (T test). Findings: The results of the analysis explain that the recruitment and selection processes have a simultaneous effect on employee performance, this is indicated by the calculated F value of recruitment (X1) on employee performance (Y) of 0.449 from F table (0.02) so that more than 0.35 the effect is stated large and significant and the value of F count selection (X2) on employee performance (Y) of 0.528 from F table (0.02) so that more than 0.35 it is stated that the effect is large and significant (Sig.) and recruitment has a partial effect on employee performance , this is indicated by the calculated T value of 0.453 which is greater than the T table of 1.96 and the significance value (P values) of 0.000 is smaller than 0.05. And selection has a partial effect on employee performance, this is indicated by the calculated T value of 0.491 which is greater than T table of 1.96 and the significance value (P values) of 0.000 is smaller than 0.05. Research limitations/implications: The limitation in this study is only to analyze the magnitude of the influence of recruitment and selection on employee performance at PT. XYZ. Originality/value: The novelty in this research is that no previous research has been found that discusses the recruitment and selection of the performance of technician employees at PT. XYZ.